2014
DOI: 10.1155/2014/603484
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Survey of Selected Bovine Pathogens in Water Buffaloes in the North Region of Brazil

Abstract: Although the largest buffalo herd in the occident is in the north region of Brazil, few studies have been conducted to assess the prevalence of selected parasitic diseases in buffalo herd. The present study was therefore conducted to investigate the epidemiological of Toxoplasma gondii, Neospora caninum, Anaplasma marginale, Babesia bigemina, and Babesia bovis in water buffaloes in the north region of Brazil. A total of 4796 buffalo blood samples were randomly collected from five provinces and simultaneously a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
(20 reference statements)
1
9
1
Order By: Relevance
“…The prevalence of antibodies against N. caninum in buffaloes was variable in the Brazilian regions. In Northern region of Brazil, were found 48.9% of 4796 buffaloes (Silva et al 2014), in the Southeastern region of Brazil was found in 64% of 222 buffaloes (Fujii et al 2001). Similar results to our study were found in Northeastern Brazil, with seropositivity 35.9% of 117 buffalo sera (Gondim et al 2007).…”
Section: Resultssupporting
confidence: 89%
“…The prevalence of antibodies against N. caninum in buffaloes was variable in the Brazilian regions. In Northern region of Brazil, were found 48.9% of 4796 buffaloes (Silva et al 2014), in the Southeastern region of Brazil was found in 64% of 222 buffaloes (Fujii et al 2001). Similar results to our study were found in Northeastern Brazil, with seropositivity 35.9% of 117 buffalo sera (Gondim et al 2007).…”
Section: Resultssupporting
confidence: 89%
“…Antibodies to T. gondii were found in 1715 (35.5%) of 4796 water buffaloes from northern Brazil. They used an in-house ELISA and the cut-off titer for IFAT was 1:40 [7]. In a report from southern Brazil, antibodies were found in 46 (27.2%) of 169 water buffaloes by IFAT; sera were run at 1:64 and 1:256 dilutions and the seropositivity results were based on a titer of 1:64 [8].…”
Section: Discussionmentioning
confidence: 99%
“…buffalo herd is in Northeast, with 10,437 thousand heads located in the state of Pernambuco (IBGE, 2016). Many serological surveys on N. caninum infection in water buffaloes have been carried out by researchers in different parts of the world with prevalences ranging from 1.50 to 88.30% (BRASIL et al, 2015;CAMPERO et al, 2007;CHRYSSAFIDIS et al, 2015;DUBEY et al, 1998;FUJII et al, 2001;FERROGLIO et al, 2003;GALVÃO et al, 2013;GONDIM et al, 2007;GUARINO et al, 2000;GENNARI et al, 2005;HUONG et al, 1998;HAMIDINEJAT et al, 2015;KONNAI et al, 2008;KONRAD et al, 2013;MEENAKSHI et al, 2007;MOORE et al, 2014;NASIR et al, 2011;NEVERAUSKAS et al, 2015;PORTELLA et al, 2016;RODRIGUES et al, 2005;ROMERO-SALAS et al, 2017;SOUZA et al, 2001;SENGUPTA et al, 2012;SILVA et al, 2010SILVA et al, , 2014SILVA et al, , 2017VOGEL et al, 2006;YU et al, 2007).…”
Section: Introductionmentioning
confidence: 99%